Мотивът за Одисей и неговите трансформации: мит и наратив в немската следвоенна литература - Пацовска-Иванова, Ева (Zeitschrift „Germanistik und Skandinavistik“ / Journal for German and Scandinavian Studies, 2021)
The article on „The Motif of Ulysses and its Transformations: Myth and Narrative in German Postwar Literature“ by Eva Patsovska-Ivanova focuses on the reception of the mythologicalmotif of Ulysses in German postwar prose and more specifically on its quality toinfluence the narratological approach of the authors. With its associative power and flexibility the myth enables them to meet the challenges of their complicated historical situation by adapting the basic mythological story to their own aesthetic purposes. The article studies the mechanisms for adapting the myth and their functions.
Keywords: Ulysses; myth; narrative; postwar literature; Germany